Cree and Christian : Encounters and Transformations - Westman, Clinton, 1971- (Book collections on Project MUSE., 2022)
"'Cree and Christian' is an ethnographic account of a contemporary Pentecostal congregation, contextualized historically and theoretically, in relation to other religious movements over time"--